Influence of Different Bryophyte Carpets on Vascular Plant Establishment Around Pools in Restored Peatlands. (10th September 2013) - Laberge, Virginie; Hugron, Sandrine; Rochefort, Line; Poulin, Monique
Abstract: Vascular plants associated to natural peatland pools do not spontaneously colonize edges of man‐made pools in restored peatlands and have proven to be recalcitrant to the usual restoration techniques. The goal of this study was to evaluate the effect of the species used as a seedbed ( Cladopodiella fluitans, Sphagnum cuspidatum, or Sphagnum magellanicum ) and its developmental stage (established carpet or newly reintroduced fragments) on establishment success in the field of the seeds of four vascular species: Carex limosa, Carex magellanica, Carex oligosperma, and Scheuchzeria palustris . The germination rate was measured after one season and growth after two seasons. Seedbed composition and developmental stage had no effect on Carex, whereas the germination of S. palustris was higher on S. cuspidatum . Growth of vascular plants was slightly improved on S. magellanicum carpets and was lower on seedbeds of C. fluitans . Our results lead us to recommend seeding at the same time as bryophyte fragments are spread and fostering introduction of Sphagnum mosses, preferably to C. fluitans, around artificial pool edges. Copyright © 2013 John Wiley & Sons, Ltd.